2021
DOI: 10.1097/aud.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Text Captioning Buffers Against the Effects of Background Noise and Hearing Loss on Memory for Speech

Abstract: Objectives. Everyday speech understanding frequently occurs in perceptually demanding environments, for example due to background noise and normal age-related hearing loss. The resulting degraded speech signals increase listening effort, which gives rise to negative downstream effects on subsequent memory and comprehension, even when speech is intelligible.In two experiments, we explored whether the presentation of realistic assistive text captioned speech offsets the negative effects of background noise and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Sommers and colleagues (Failes et al, 2020;Failes & Sommers, 2022;Rogers, 2017;Rogers et al, 2012;Rogers & Wingfield, 2015;Sommers et al, 2014) have typically used a -10 or -15 SNR or have used an SNR that correlates with participants' 50% speech reception threshold performance (i.e., the SNR that yields 50% accuracy on a word identification task). In contrast, our +3dB SNR has been shown in prior work to lead to high levels of intelligibility, especially for young normal-hearing listeners (see Payne et al, 2022;Silcox & Payne, 2021). Thus, Experiment 1 shows that even when the listener has the speech presented in relatively good SNR, they are still susceptible to occasional false hearing.…”
Section: Experiments 1 Discussionmentioning
confidence: 52%
“…Sommers and colleagues (Failes et al, 2020;Failes & Sommers, 2022;Rogers, 2017;Rogers et al, 2012;Rogers & Wingfield, 2015;Sommers et al, 2014) have typically used a -10 or -15 SNR or have used an SNR that correlates with participants' 50% speech reception threshold performance (i.e., the SNR that yields 50% accuracy on a word identification task). In contrast, our +3dB SNR has been shown in prior work to lead to high levels of intelligibility, especially for young normal-hearing listeners (see Payne et al, 2022;Silcox & Payne, 2021). Thus, Experiment 1 shows that even when the listener has the speech presented in relatively good SNR, they are still susceptible to occasional false hearing.…”
Section: Experiments 1 Discussionmentioning
confidence: 52%
“…This hypothesis would be generally consistent with the work published by (Zekveld et al 2009b), who reported more text benefits for people with larger working memory capacities, suggesting working memory capacity is important for using supplemental text. Conversely, Payne et al (2022) assessed behavioral listening effort and suggested that simultaneous text supplementation can be beneficial to long-term sentence recognition memory in auditory-only tasks. More investigations need to be done with behavioral or physiologic listening effort paradigms to evaluate whether benefiting from text is fully effortless in more complex audiovisual tasks where facial cues are also available.…”
Section: Discussionmentioning
confidence: 99%